2020
DOI: 10.1037/ipp0000140
|View full text |Cite
|
Sign up to set email alerts
|

National Travel Assistance Entitlements Are Inaccessible to Whānau Māori

Abstract: New Zealand’s National Travel Assistance scheme is intended to provide financial support for people who need to either travel frequently or over long distances for specialist health care treatment. Taking an Indigenous Psychology orientation to “away-from-home” hospital admissions, we broaden the focus beyond an individual’s physical experience of hospitalization to the wider social and political context. Based on our research, we recommend a whānau-centered approach to travel assistance that will offer better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…As reported in previous research, for these whānau, this new trajectory, te ao hurihuri, was an emotional roller coaster, as they encountered new medical terminology, foreign environments, and uncertainties [ 17 , 18 , 19 ]. At the same time, accessing non-medical support, such as transport and even meals was often overly complicated and frustrating [ 12 , 56 ]. Whānau were left feeling anxious and unprepared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in previous research, for these whānau, this new trajectory, te ao hurihuri, was an emotional roller coaster, as they encountered new medical terminology, foreign environments, and uncertainties [ 17 , 18 , 19 ]. At the same time, accessing non-medical support, such as transport and even meals was often overly complicated and frustrating [ 12 , 56 ]. Whānau were left feeling anxious and unprepared.…”
Section: Discussionmentioning
confidence: 99%
“…Personnel involved in whānau transfers to a tertiary hospital have reported systems seemingly designed for clinical and administrative ease rather than to meet the needs of whānau [ 10 ]. Whānau have identified issues related to anxiety, foreign environments, isolation, lack of autonomy, difficulties in accessing government-funded travel assistance, and lack of appropriate information sharing [ 12 , 13 ]. Internationally, similar issues have been reported with non-Indigenous women transferred to tertiary services prior to or following birth [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, schemes such as the NTA should provide patients and/or their whānau with up-front funding (rather than relying on reimbursement systems), with this funding to be set at an appropriate level that recognises both the direct and indirect costs associated with travelling for cancer care. We also need to ensure that whānau are aware of what funding is available and understand how to access it [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examining national level hospitalisation data across six years (2009-2014), the authors found that around 10% of all Māori hospital admissions-and more than 25% of all Māori hospital transfers-took place outside of the District Health Board (DHB) where the person lived. 5 In other words, one in ten Māori hospitalisations (and a quarter of all transfers between hospitals) required Māori to travel to a hospital that was outside their home region. With more than a million hospitalisations among Māori over the six-year study period, the cumulative demand placed on individuals and their whānau-the transport costs, the accommodation for supporting whānau, the organisation of childcare or elderly care for those left back at home-is difficult to fathom.…”
mentioning
confidence: 99%